Efficacy and safety evaluation of alcohol-containing and alcohol-free mouth rinses: A clinical study (Bangladesh Journal of Medical Science, 2024)
Background: This clinical study aims to evaluate the efficacy and safety of alcohol-containing and alcohol-free mouth rinses in a controlled setting. With oral hygiene being a crucial aspect of overall health, it is essential to determine which type of mouth rinse is more effective and safer for daily use.Materials and Methods: A randomized, double-blind, parallel-group study was conducted with 150 adult participants. They were divided into two groups: one using an alcohol-containing mouth rinse, and the other using an alcohol-free alternative. Participants followed a standardized oral hygiene regimen for four weeks, using their respective mouth rinses twice daily. Key parameters such as plaque reduction, gingival health, and adverse effects were assessed at baseline and after the study period.Results: The results indicated a significant reduction in plaque accumulation in both groups, with the alcohol-containing mouth rinse group showing a mean reduction of 25.4% and the alcohol-free group showing a mean reduction of 23.1%. In terms of gingival health, both groups demonstrated improvement, with the alcohol-containing mouth rinse group showing a mean reduction of gingival inflammation by 19.2%, while the alcohol-free group exhibited a reduction of 18.5%. Importantly, the alcohol-free mouth rinse group reported fewer cases of adverse effects such as dry mouth and irritation compared to the alcohol-containing group.Conclusion: This clinical study suggests that both alcohol-containing and alcohol-free mouth rinses are effective in reducing plaque accumulation and improving gingival health when used as part of a daily oral hygiene routine. However, the alcohol-free mouth rinse demonstrated a lower incidence of adverse effects, making it a potentially safer choice for individuals with sensitivity or a history of irritation. Further long-term studies are needed to confirm these findings.Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S97-S100